2022
DOI: 10.1021/acs.iecr.2c01623
|View full text |Cite
|
Sign up to set email alerts
|

Power Consumption and Energy Dissipation Rate Reduction in Agitated Tanks by Control Rods Attached to a Pitched Blade Impeller

Abstract: The effects of axially symmetric control rods added to the archetypal four-blade pitched blade turbine (PBT) have been evaluated. The convectional PBT and two control rod configurations were tested (P2 and P3). Modifications resulted in a significant improvement in the hydrodynamic performance of the PBT impeller. Experimental measurements of torque and mixing time have been obtained, as well as flow measurement through particle image velocimetry (PIV) techniques to validate and compare the results obtained th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The first plane allows us to get details of the flow stream, while the P2 plane was used to evaluate the external flow around the blade profiles. The estimated error in these measurements was ≤3.5% in all cases …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first plane allows us to get details of the flow stream, while the P2 plane was used to evaluate the external flow around the blade profiles. The estimated error in these measurements was ≤3.5% in all cases …”
Section: Methodsmentioning
confidence: 99%
“…Also, the use of two types of coaxial impellers has been proposed to take advantage of the hydrodynamic characteristics of each one. , Commonly, the improved impellers contain tailored blade profiles capable of increasing mixing efficiency and reducing power consumption. A large part of such studies come from the design of turbines for pumps and hydrokinetic turbines, where the focus has been on improving the blade by incorporating hydrofoil elements such as flaps on the trailing edge or flanges on the leading edge. , Some previous research works have explored impeller blade modifications mainly using microgrooves on the blade surface, adding bladelets in a semi-open impeller in centrifugal pump applications, and attaching control rods to the impeller in mixing applications to obtain improvements in their hydrodynamic performance and power consumption reduction.…”
Section: Introductionmentioning
confidence: 99%
“…10−12 In addition, inside the vessel, the energy dissipation rate and as a result k L are enhanced at higher impeller speeds because of an increase in the intensity of the fluid flow inside the aerated reactor. 13 By maintaining the dimensionless energy dissipation rate constant, the mass transfer rate obtained by a mixer could be preserved upon scale-up because the energy dissipation rate is an indicator of the bubble breakage and coalescence. Hence, both k L and a for the large-scale aerated mixer could be predicted using the data of the small-scale mixer.…”
Section: Introductionmentioning
confidence: 99%
“…The gas–liquid interfacial area increases by breaking the bubbles into smaller sizes as the impeller speed is increased. It has been reported that the interfacial area has a significant effect on the mass transfer rate. In addition, inside the vessel, the energy dissipation rate and as a result k L are enhanced at higher impeller speeds because of an increase in the intensity of the fluid flow inside the aerated reactor . By maintaining the dimensionless energy dissipation rate constant, the mass transfer rate obtained by a mixer could be preserved upon scale-up because the energy dissipation rate is an indicator of the bubble breakage and coalescence.…”
Section: Introductionmentioning
confidence: 99%